Private‐Public Partnership: improved bean seed access in Malawi - Rubyogo, Jean-Claude; Magreta, R.; Chirwa, Rowland; Mazuma, E.; Andrews, M. (Pan-Africa Bean Research Alliance, 2012)
This initiative was aimed at demonstrating that the public‐private partnerships in the bean seed value chain can make a difference to avail bean seed of improved varieties to farmers. The common beans is an import food crop covering an estimated area of 260,000 ha in Malawi in 2010. However the reliable system for access to quality seed of improved bean varieties is still constrained by lack of sustainable supply. Through a public‐private partnership (PPP), CIAT‐DARS and DS Ltd shared seed system related roles, which generated about 1040 tons between 2009‐11, reaching 590,000 smallscale farmers with seed of improved bean varieties. An evaluation carried out to assess the outcomes, revealed that sustained provision of foundation seeds through diversified sources (both private and public), technical support/backstopping from extension staff and researchers to private seed suppliers was essential in establishing an efficient and sustainable seed supply system.